2016
DOI: 10.1136/bmjopen-2015-008973
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of Chinese herbal medicine Duhuo Jisheng decoction for knee osteoarthritis: a systematic review of randomised clinical trials

Abstract: ObjectivesDuhuo Jisheng decoction (DJD) is considered beneficial for controlling knee osteoarthritis (KOA)-related symptoms in some Asian countries. This review compiles the evidence from randomised clinical trials and quantifies the effects of DJD on KOA.Designs7 online databases were investigated up to 12 October 2015. Randomised clinical trials investigating treatment of KOA for which DJD was used either as a monotherapy or in combination with conventional therapy compared to no intervention, placebo or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 53 publications
1
53
0
Order By: Relevance
“…Loganic acid decreased proinflammatory cytokines in hypercholesterolemic rabbits [62,63] . Paeoniflorin is able to suppress inflammation in experimental arthritis by inhibiting abnormal proliferation of lymphocytes and synoviocytes and the production of proinflammatory cytokines and chemokines, nitric oxide, vascular endothelial growth factor (VEGF), and GM-CSF by synoviocytes [19,[64][65][66] . Ferulic acid, isolated from chuanxiong and danggui [67] has antioxidative and anti-inflammatory effects [67,68] .…”
Section: Discussionmentioning
confidence: 99%
“…Loganic acid decreased proinflammatory cytokines in hypercholesterolemic rabbits [62,63] . Paeoniflorin is able to suppress inflammation in experimental arthritis by inhibiting abnormal proliferation of lymphocytes and synoviocytes and the production of proinflammatory cytokines and chemokines, nitric oxide, vascular endothelial growth factor (VEGF), and GM-CSF by synoviocytes [19,[64][65][66] . Ferulic acid, isolated from chuanxiong and danggui [67] has antioxidative and anti-inflammatory effects [67,68] .…”
Section: Discussionmentioning
confidence: 99%
“…A. bidentata can strengthen the waist and knee, by eliminating stagnation, removing blood stasis, and nourishing the liver and kidney. Chinese herbal medicine formulas containing A. bidentata have been used in clinical practice for thousands of years, such as Duhuo Jisheng decoction [27] and SiMiaoFang [28]. A. bidentata is used to eliminate inflammation or improve circulation of the knees.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe OA suffer from joint deformity and loss of joint function [1,2]. Epidemiological statistical results showed that the prevalence of OA in patients aged over 40 years old in China was about 30, and 60%-70% among patients aged above 65 years [3,4]. With the aging of Chinese population, the occurrence of OA is increasing and becomes a serious social and public health problem.…”
Section: Introductionmentioning
confidence: 99%